1870 S. C. Acts p. 403, no. 288, §4 - (:unkn) unknown (My University, 1870)
Granted "Trial Justices" the authority to arrest all "affrayers, rioters, disturbers and breakers of the peace, and all who go armed offensively to the terror of the people." Including those who make threatening speeches, dangerous person, and disorderly persons.
Keywords: GOING ARMED